Toxicity Studies of Oxy Powder®-Revised - JOGENDER K. LALLA; MEENA U.SHAH; EDWARD F III GROUP (International Journal of Pharma and Bio Sciences, 2010)
The objective of this study was to assess the toxic effects of Oxy powder® in-vitro on four pathogenic microbes and a probiotic bacterium generally present in the human GI tract and to determine acute oral toxicity (LD50) profile of Oxy Powder® in Sprague Dawley rats. The results shall be used in selecting doses in repeated dose toxicity study of Oxy Powder.